1998
DOI: 10.1046/j.1365-2214.1998.00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Educating young children about asthma: comparing the effectiveness of a developmentally appropriate asthma education video tape and picture book

Abstract: Asthma self-management programmes have been shown to increase children's knowledge about asthma and improve their management practices and health status. However, existing programmes have rarely addressed the unique learning needs of very young children. This study aimed to develop and assess the effectiveness of a video tape and picture book designed to teach children about the prevention and management of acute episodes of asthma. The information content of the educational resources was determined by analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
7

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 26 publications
1
60
0
7
Order By: Relevance
“…Considering the health promoting value of active child participation [6,7], it is important to be aware of the (non)particpatory in¯uence of adult behavior in doctor± parent±child interactions. Only by collaboratively creating a developmental environment, both GP and parent may give children a voice in triadic medical encounters.…”
Section: Practice Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the health promoting value of active child participation [6,7], it is important to be aware of the (non)particpatory in¯uence of adult behavior in doctor± parent±child interactions. Only by collaboratively creating a developmental environment, both GP and parent may give children a voice in triadic medical encounters.…”
Section: Practice Implicationsmentioning
confidence: 99%
“…However, it is increasingly being acknowledged that children can provide information themselves and should be involved in decisions about their own health care [4,5]. In addition, empirical studies have shown the health-promoting value of active child participation [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, young children themselves may benefit from asthma education and practical training in skills. One study found that children aged 2-5 yrs who were exposed to a developmentally appropriate educational intervention that included a picture book and video tape showed improved asthma knowledge, as well as better compliance and health, compared to controls [94].…”
Section: Parent and Patient Educationmentioning
confidence: 99%
“…Since combining traditional and new technological methods has been shown to produce the best information retention, developing new educational methods has become an emerging area of study. [69,70]. Specifically, the use of story to enhance communication and boost education methods is supported in the literature [67,[70][71][72][73].…”
Section: Technology and Educationmentioning
confidence: 68%
“…Holzheimer, Mohay, and Masters' study comparing the effectiveness of books versus videotaped materials found that videos were not as useful as books that allow children to self-pace and better understand the material [70]. Still, the idea of using electronic media for education fueled further research regarding electronic books, also called CD-ROM storybooks, talking books, interactive books, or computer books [74].…”
Section: Technology and Educationmentioning
confidence: 99%